2017
DOI: 10.3390/ijms18112299
|View full text |Cite
|
Sign up to set email alerts
|

Relation among Aromatase P450 and Tumoral Growth in Human Prolactinomas

Abstract: The pituitary gland is part of hypothalamic-pituitary–gonadal axis, which controls development, reproduction, and aging in humans and animals. In addition, the pituitary gland is regulated mainly by hormones and neurotransmitters released from the hypothalamus and by systemic hormones secreted by target glands. Aromatase P450, the enzyme responsible for the catabolization of aromatizable androgens to estrogens, is expressed in different parts of body, including the pituitary gland. Moreover, aromatase P450 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 147 publications
(185 reference statements)
2
9
0
Order By: Relevance
“…Although the role of estrogen in the genesis of GH-secreting adenomas is less certain, some data suggest locally produced estrogen through aromatization might alter GH synthesis and secretion in both men and women [3,37,38]. Likewise, aromatase expression has been shown in both normal and neoplastic pituitary [3][4][5][6][7]36]. In our study, similar to our [4] and others' [7] previous findings, we detected increased aromatase protein expression in patients with GH-secreting adenoma as compared to those with NFA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the role of estrogen in the genesis of GH-secreting adenomas is less certain, some data suggest locally produced estrogen through aromatization might alter GH synthesis and secretion in both men and women [3,37,38]. Likewise, aromatase expression has been shown in both normal and neoplastic pituitary [3][4][5][6][7]36]. In our study, similar to our [4] and others' [7] previous findings, we detected increased aromatase protein expression in patients with GH-secreting adenoma as compared to those with NFA.…”
Section: Discussionsupporting
confidence: 89%
“…There is emerging evidence that estrogenic exposure might have a role in the development of different types of pituitary tumors, namely prolactinomas [6,15,36]. Although the role of estrogen in the genesis of GH-secreting adenomas is less certain, some data suggest locally produced estrogen through aromatization might alter GH synthesis and secretion in both men and women [3,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of aromatase overexpression and knockout transgenic mice models confirmed that estradiol is largely responsible for the maintenance of the population of lactotropic cells in males [32,33], apart from playing an essential role in the hypothalamus-pituitary regulation of testicular and associated functions [18,34]. With regard to aromatase expression in pituitary adenomas and its possible association with tumor subtype, sex and/or tumor size, the results are still confounding [29,[35][36][37] and await further multimethodological confirmation and testing. Of note, clinical management of hypogonadism in men with macroprolactinoma, which was refractive to dopamine agonists, required aromatase inhibitor treatment in addition to testosterone replacement, to prevent the secondary rise in PRL and, finally, the potential for tumor enlargement [38].…”
Section: Estrogen Signaling In the Anterior Pituitary And Prolactinommentioning
confidence: 99%
“…89 Aromatase P450 is an enzyme that is expressed in different parts of the body, and changes in its level in the body cause different diseases. 90 Different NPs induce apoptosis in cancer cells through the regulation of the JNK pathway. [91][92][93] The oxidative stress generated in SMMC7721 cells with Pue treatment due to ROS causes JNK activation, which causes c-jun inhibition and cell apoptosis.…”
Section: C-jun Nh2 Terminal Kinase (Jnk) Pathwaymentioning
confidence: 99%